General paresis of the insane - A rare case report - Ganga vellaisamy, Seethalakshmi; Murugan, Subramania Adityan (Journal of Pakistan Association of Dermatologists, 2020)
General Paresis of the Insane (GPI) is a meningoencephalitis as a result of direct invasion of Treponema pallidum into the cerebrum, typically develops between 15 and 20 years after initial infection. Mr. X is a 50 year old painter referred to Venereology Department from Neurology Department with 3 years history of gradually progressive behavioural disturbances along with disturbances in speech & difficulty in writing. Blood VDRL & CSF VDRL was found to be reactive. A diagnosis of GPI was made and the patient was treated appropriately. He showed remarkable improvement following treatment. Â  Â 